Osteotomy Techniques in Preservation Rhinoplasty with an Analysis of a Radix–Skull Base Computed Tomography Series - Neves, José C.; Abdulraheem, Maryam; Neves, Ligia; Flora, Barbara; D'Souza, Alwyn (Facial Plastic Surgery, 2024)
This study aims to explain our experience with dorsal preservation osteotomies, focusing on transverse, lateral, and dorsal aesthetic lines (DAL) osteotomies. We describe the utilization of a variety of surgical instruments, including osteotomes, saws, burrs, and piezo. This paper describes our concept of transcutaneous ultrasonic osteotomy, microedged-specific osteotomy, applying drills for lateral wall reshaping, and integrating piezo technology to establish new DAL. Furthermore, we present a radix–skull base computed tomography series analysis to evaluate the safety of transverse and radix osteotomies.
Keywords: DAL osteotomies; radix osteotomy; TUO; MESO; skull base trauma